Peran penting bank efficiency dalam memediasi pengaruh income diversification dan bank liquidity terhadap bank performance - Utami, Riska Amalia; Nabhan, Faqih (Journal of Accounting and Digital Finance, 2022)
This study aims to determine the effect of income diversification and bank liquidity on bank performance with bank efficiency as an intervening variable in Islamic Commercial Banks in Indonesia in 2010-2019. The results show that income diversification has a positive and insignificant effect on bank performance, bank liquidity has a positive and insignificant effect on bank performance, income diversification has a positive and significant effect on bank efficiency, bank liquidity has a positive and insignificant effect on bank efficiency, bank efficiency has a negative and significant effect on bank efficiency.